Incidental Adrenal Oncocytic Neoplasm of Uncertain Malignant Potential in HIV Patient: A Clinical Approach - Nisa, Zaibun (Issues and Development in Health Research Vol. 7, 2021)
Objectives: The objectives of this article are to highlight the importance of clinicopathological correlation in the diagnosis of a rare non-functional adrenal tumour in HIV patient with Pseudo-Cushing’s syndrome. The presence of cortisol excess in the background of adrenal neoplasm indicated a radiological diagnosis of adrenocortical carcinoma. However, the histology showed an oncocytic tumour of uncertain malignant potential and high cortisol levels in blood, which remained elevated even after removal of the tumour. Ideally, these tumours are non-functional and are not related with increase in cortisol levels. But the histological diagnoses were not correlating with the biochemical findings. After thorough search through previous medical history, it was found that the patient was a known HIV case on antiretroviral therapy. Finally, keeping everything in perspective, it was concluded that the hypercortisolemia was related to antiretroviral drug therapy and the tumour per se was a rare incidental, non-functional tumour. The take home message was therefore, without proper clinical knowledge of drug therapy and HIV status of the patient, the diagnosis of a non-functional adrenal tumour in the presence of features of hypercortisolemia would have been questionable. Introduction: We present a 70year old, HIV positive gentleman with a non-functional oncocytic adrenal neoplasm of uncertain malignant potential showing manifestation of Pseudo-Cushing’s syndrome. Methods: Most of the data were collected from institutional clinical reports and radiological findings. These were compiled and compared with previous case reports on adrenal manifestations in HIV patients. Results: It was found that HIV patients show varied endocrine manifestations ranging from adrenal, testicular, pituitary, pancreatic and thyroid abnormalities. The adrenal disorders mainly include adrenal insufficiency due to opportunistic infections or by tumours such as Kaposi’s sarcoma or Non-Hodgkin’s lymphoma (NHL). Incidental adrenal oncocytic neoplasm of borderline malignant potential has not been reported till date in HIV patients. Conclusion: A very rare tumour seen in HIV patient presenting with Pseudo-Cushing’s syndrome.